Effect of different Substrate supplements on the growth and yield of two species of Mushroom Pleurotus florida and P. sajor-caju. - Singh, Saurabh Deep; Prasad, Ganesh (International Multidisciplinary Research Journal, 2012)
The present experiment entitled â€œresponse of mushroom (Plurotus spp.) to various substrate supplementsâ€ was under taken with the aim to determine the morpholigcal parameters and to evaluate different Pleurotus spp. For this investigation, two species of Plurotus viz. P. sajor-caju and P. floridawere taken. The cultures of these speices were multiplication potato dextrose agar medium (PDA. Yield performance of Pleurotus sajor caju and P. florida over different substrate using different supplements was studied. Pleurotus sajor-caju produced maximum yield of (719.2 g) on wheat straw substrate with soybean flour supplement @ 5%Â (SF @ 5%).With the same supplement i.e. SF @ 5%, Pleurotus florida produced the maximum yield of 690.00 g on wheat straw substrate.